Trade Interdependence of Greater Mekong Sub Region Countries - Mohammad Affendy, Arip; Puah, Chin Hong (2011)
Since 1992, the Asian Development Bank has provided various development projects under the official development assistance (ODA) to boost economic activities in Greater Mekong Sub-region (GMS). With the completion of some of major projects, we expect these countries to show interdependencies of vertical and horizontal integrated of trade. Against this background, this paper aims to clarify the causal relation of export activities between the five countries of GMS i.e. Thailand,Vietnam, Myanmar, Cambodia, and Laos. For this purpose we run the Toda-Yamamoto causality test on quarterly data from 1990 to 2009.The results suggest the followings. The Toda and Yamamoto (1995) test results indicate different causality pattern among the GMS countries in export and FDI flows. Differences in their causality pattern is determine by combination of several factor, such as differences in income per capita, internal and international political condition, and membership in socioeconomic and political cooperation such as ASEAN.